Determination of Surface Area of Head for Biomedical and other Applications - Rao, S. S.; Papukutty, K. K.; Bhat, T. Balakrishna (Defence Science Journal, 2013)
A simple, rapid and reproducible method has been devised for measuring the surface area of the head relevant for armour design. In this method, the following stages are involved: (i) securing a kraft paper over the head with the help of elastic band, (ii) tightly folding the paper wherever necessary to make a snug contour-matched paper dome, (iii) marking the folded areas with lines, (iv) spreading the paper and cutting out areas within the folds and the area filling outside the marked periphery of interest, (v) weighing the cut-out pieces and few pieces of known area from the same sheet, and finally (vi) calculating the head-surface area. Preliminary data on 12 volunteers indicated that head-surface area has no significant correlation with their age, total body-surface area calculated from height and weight or with the circumference of their heads. A significant and positive correlation was found with cephalic length. The new method can find application in biomedical studies and head gear designs (e.g. helmets).